(untitled) (Journal of Pharma Insights and Research, 2025)
Nitrate contamination in water resources is a significant environmental and public health challenge globally. This review provides the current knowledge about nitrates in water systems, their sources, detection methods, and health effects. Nitrates, predominantly entering water systems through agricultural runoff, wastewater discharge, and industrial effluents, pose substantial health risks when present in drinking water above permissible limits. The transformation of nitrates to nitrites in the human body can lead to serious health conditions, including methemoglobinemia and potential carcinogenic effects. Various detection methods, ranging from simple colorimetric tests to modern analytical techniques, enable monitoring of nitrate levels in water sources. The effectiveness of remediation measures, particularly reverse osmosis systems, show variable success rates in nitrate removal, with recent studies indicating approximately 85% removal efficiency. It can be concluded that there is a crucial need for regular monitoring, implementation of effective water treatment, and development of innovative solutions to address nitrate contamination in water resources, ensuring safe drinking water accessibility for populations worldwide.